Synthesis and characterization of highly transparent and conductive SnO2:F and In2O3:Sn thin films deposited by spray pyrolysis - Riveros,R. (2006)
Highly transparent and conductive thin films of SnO2:F and In2O3:Sn (ITO) have been prepared on glass substrates using the simple pyrolitic (spray) method. Through an exhaustive parameter study and using as diagnostic method for the film quality a figure of merit defined as a function of both, the transmittance and the electric resistivity, the conditions to prepare the SnO2:F and ITO films, with adequate properties to be used as transparent front contact for solar cells, were achieved. A relevant contribution of this work is related with the deposition of SnO2:F and ITO films with the mentioned characteristics, using a solution synthesized in our laboratory by dissolving the precursor metals in HCl. Transparent conducting oxide (TCO) thin films were obtained, with transmittances greater than 80% and resistivities smaller than 7x10- 4 omega·cm, results which are comparable with those obtained using commercial reactants. Results concerning the influence of the synthesis parameters on the optical, electrical and structural properties of the TCO films are reported.